Human, All Too Human: Mariology As Theo-Philosophical Anthropology - Terry, Joseph (2023)
Implicit within the human being as such are mysteries, which can be formulated into certain questions (What is the human being? What is the vocation of such a being? From where does it originate? What is its destiny, its telos?), that theological and philosophical anthropology seeks to address. Historically, theologically informed anthropological investigation has produced a good deal of research into some of these mysteries, but either to the exclusion of Mary, Mother of Jesus, or inclusive of her but narrowly construed. This research project aims to investigate these mysteries in and through the person of Mary, Mother of God-anthropos, in order to elucidate the overall mystery of the human being and so discover how Our Lady uniquely and decisively illumines and illustrates what it means to be human Theo-philosophically. The following objectives are, thus, pursued in this study: (1) Identifying a metaphysical basis for situating anthropological research under Mariology; (2) identifying how both a theological and philosophical consideration of Our Lady in view of anthropology is justified given such a metaphysical basis; (3) indicating how the Church’s four Marian dogmas address those questions implicit in anthropos, questions pertaining to human origin, identity, vocation, and destiny; and, finally, (4) exploring the various ways in which a Theo-philosophical anthropology predicated on Mariology reveals Mary, in synergistic partnership with her Son, to be the theoanthropocosmic synthesis as a mere human. Therefore, by systematizing the dogmatic truths of Mary in view of anthropological considerations, and by doing so within the dual methodological approaches of theology and philosophy, this study offers a framework by which we can adjudicate distinct and sometimes dispersive insights into the nature of anthropos that can be brought together under a meta-anthropology illumined by the content of revelation (via theology) and explicated (via philosophy).